Scale dependent drivers of wild bee diversity in tropical heterogeneous agricultural landscapes. Issue 19 (9th September 2016) - Basu, Parthiba; Parui, Arpan Kumar; Chatterjee, Soumik; Dutta, Aditi; Chakraborty, Pushan; Roberts, Stuart; Smith, Barbara
Summary: Factors associated with agricultural intensification, for example, loss of seminatural vegetation and pesticide use has been shown to adversely affect the bee community. These factors may impact the bee community differently at different landscape scales. The scale dependency is expected to be more pronounced in heterogeneous landscapes. However, the scale‐dependent response of the bee community to drivers of its decline is relatively understudied, especially in the tropics where the agricultural landscape is often heterogeneous. This study looked at effects of agricultural intensification on bee diversity at patch and landscape scales in a tropical agricultural landscape. Wild bees were sampled using 12 permanent pan trap stations. Patch and landscape characteristics were measured within a 100 m (patch scale) and a 500 m (landscape scale) radius of pan trap stations. Information on pesticide input was obtained from farmer surveys. Data on vegetation cover, productivity, and percentage of agricultural and fallow land (FL) were collected using satellite imagery. Intensive areas in a bee‐site network were less specialized in terms of resources to attract rare bee species while the less intensive areas, which supported more rare species, were more vulnerable to disturbance. A combination of patch quality and diversity as well as pesticide use regulates species diversity at the landscape scale (500 m), whereas pesticide quantity drove diversity at the patch scale (100 m). At the landscape scale, specialization of each site in terms of resources for bees increased with increasing patch diversity and FL while at the patch scale specialization declined with increased pesticide use. Bee functional groups responded differentially to landscape characteristics as well as pesticide use. Wood nesting bees were negatively affected by the number of pesticides used but other bee functional groups were not sensitive to pesticides. Synthesis and Applications : Different factors affect wild bee diversity at the scale of landscape and patch in heterogeneous tropical agricultural systems. The differential response of bee functional groups to agricultural intensification underpins the need for guild‐specific management strategies for wild bee conservation. Less intensively farmed areas support more rare species and are vulnerable to disturbance; consequently, these areas should be prioritized for conservation to maintain heterogeneity in the landscape. It is important to conserve and restore seminatural habitats to maintain complexity in the landscapes through participatory processes and to regulate synthetic chemical pesticides in farm operations to conserve the species and functional diversity of wild bees. Abstract : The study deals with wild bee species diversity along an agricultural intensification gradient in Eastern India and reports effects of scale‐driven drivers on bee diversity in tropical heterogeneous landscapes. The novelty of this study is in its focus on factors impacting wild bee diversity at the landscape as well as the farm scale in a tropical landscape in India that is equally relevant in other tropical countries. The study also highlights the effect of various scale specific drivers on the wild bee nesting guilds and recommends scale and guild‐specific pollinator management strategies.